2006
DOI: 10.1158/1078-0432.ccr-06-1520
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Signaling Pathways: Therapeutic Perspective

Abstract: The establishment of a vascular supply is one of the earliest and most important events occurring during embryonic development. Growth and maturation of a functional vascular network are complex and still incompletely understood processes involving orchestrated activation of vascular progenitors in the early stages of embryonic development followed by vasculogenesis and angiogenesis. These processes require a tightly regulated activation of several growth factors and their receptors. The role of vascular endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
202
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(208 citation statements)
references
References 57 publications
1
202
0
5
Order By: Relevance
“…2 is a crucial regulator of vasculogenesis, angiogenesis, and vascular permeability (1)(2)(3)(4)(5). A number of studies have suggested that VEGF promotes proliferation, migration, and survival of endothelial cells (1,4).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
See 2 more Smart Citations
“…2 is a crucial regulator of vasculogenesis, angiogenesis, and vascular permeability (1)(2)(3)(4)(5). A number of studies have suggested that VEGF promotes proliferation, migration, and survival of endothelial cells (1,4).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…A number of studies have suggested that VEGF promotes proliferation, migration, and survival of endothelial cells (1,4). VEGF (also termed VEGF-A) is a member of the growth factor subfamily that includes VEGF-B, -C, -D, and -E and placental growth factor (PlGF).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF-A promotes angiogenesis, and belongs to the VEGF family of proteins, which also includes VEGF-B, VEGF-C, VEGF-D and placental-derived growth factor [2]. There are many isoforms of VEGF-A that are named according to their number of amino acids, i.e.…”
Section: Vegf Within the Glomerulusmentioning
confidence: 99%
“…VEGF is a potent proangiogenic factor that stimulates endothelial cell proliferation, migration and tube formation - key processes of angiogenesis [23]. The biologically relevant VEGF signaling events are mainly mediated by VEGFR-2 [24,25,26]. Activation of VEGFR-2 contributes to the phosphorylation of multiple downstream signals including ERK, JNK, PI3K, AKT, P70S6K and p38MAPK that subsequently promote the proliferation migration and tube formation of endothelial cells [24].…”
Section: Discussionmentioning
confidence: 99%